Effect of Cryopreserved Cord Blood Serum on Reparation Processes in Rat Brain Tissue With Acute Focal Cerebral Ischemia - Lychko, Volodymyr S.; Malakhov, Volodymyr O.; Sukach, Oleksandr M. (Problems of Cryobiology and Cryomedicine, 2019)
The research was performed to investigate the possibility of stimulating reparative processes in rats with acute focal cerebral ischemia (AFCI) by administering the cryopreserved cord blood serum (CCBS) of human. A comparative morphometric analysis of the structural components of the cerebral cortex sensor-motor area was conducted in dynamics of treatment. The development of a potent neurotoxic effect during the AFCI was confirmed by qualitative and quantitative indices, in particular by the 4.57 times increase of alterational and in 3.62 times of the perineural satellite indices relative to the control. Degenerative processes were accompanied with powerful microcirculatory changes associated with the brain tissue swelling, as evidenced by a rise in average area of perivascular spaces by 45 times versus intact animals and pronounced secondary spasm of the vessels. The use of CCBS stimulated reparative processes in the necrotic zone by increasing the capillary density by 21.8% if compared to intact animals and prevented the development of the blood-brain barrier and membrane-receptor complex dysfunction. Probl Cryobiol Cryomed 2019; 29(3): 277–290.